PERAN COMMISION FOR THE CONSERVATION OF SOUTHERN BLUEFIN TUNA (CCSBT) DALAM PENGENDALIAN PENANGKAPAN TUNA SIRIP BIRU SELATAN DI INDONESIA - Ananda Febriansyah Herlambang, (2022)
Indonesia has a variety of marine wealth ranging from biological and non-biological resources, one of Indonesia's greatest wealth comes from fisheries. Fisheries also consist of various types, but Southern Bluefin Tuna (SBT) is a species that is considered to need more attention. There has been an overexploitation of SBT which has caused the availability of SBT to be depleted and difficult to find and is considered to have reached the urgency to implement conservation measures. In addition, SBT is a species that has a high selling price which if it can be used optimally it will provide many benefits for Indonesia. Therefore, Indonesia needs to cooperate with other parties to be able to improve control over SBT. In dealing with this problem, Indonesia took steps to join the regional tuna fisheries organization, namely the Commission for the Conservation of Southern Bluefin Tuna (CCSBT). This study analyzes the role played by CCSBT to help Indonesia improve the control, management and management of SBT in 2016-2021. The researcher uses the theory of International Organization (OI) proposed by Clive Archer, which divides the roles of OI, namely instruments, arenas and actors to be able to analyze the roles played by CCSBT. The research data were obtained through interviews (in depth interviews) and literature studies which were then analyzed using qualitative methods presented in descriptive form. This study found that CCSBT was successful in controlling the SBT catch rate in Indonesia, and Indonesia was able to implement CCSBT regulations well so that it made Indonesia interested in its interests. The role of CCSBT is significant in Indonesia's interests, in the interest of improving SBT control, realizing SBT conservation actions, expanding economic networks, and strengthening Indonesia's position in international fisheries. Keywords : CCSBT, international organizations, southern bluefin tuna, Indonesia